Analysis of Potential Hazards in Pipe Receiving Work Using the Job Safety Analysis (JSA) Method and the ISO 45001 Approach at PT. XYZ - Robby Wijaya; Rachmasari Pramita Wardhani; Maeka Dita Puspa Syamtinningrum (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Pipe receiving is one of the operational activities with a high potential for occupational hazards because it involves unloading, lifting, transporting, and storing pipes using lifting equipment, as well as direct interaction between workers and heavy materials. Unsystematic hazard identification and control can increase the risk of workplace accidents, material damage, and operational disruption. This study aims to identify potential hazards at each stage of the pipe receiving process using the Job Safety Analysis (JSA) method and to evaluate its conformity with the ISO 45001:2018 approach at PT. XYZ. A descriptive method with a qualitative approach was employed. Data were collected through direct observation, interviews with workers and HSSE personnel, and documentation studies. The findings indicate that the pipe receiving process consists of ten work stages with various hazards, including being struck by materials, caught between objects, slipping, falling loads, and collisions with lifting equipment. Recommended control measures include toolbox meetings, equipment inspection, safe work procedures, barricade installation, improved compliance with Personal Protective Equipment (PPE), and regular supervision. The controls applied at PT. XYZ are generally consistent with Clauses 6.1.2, 8.1, and 9.1 of ISO 45001:2018, although continuous improvement in supervision and evaluation is still required.